Deterministic Malaria Transmission Model with Acquired Immunity - Jane, Labadin; C. Kon, M. L.; S. F. S., Juan (2009)
This paper focuses on the development of a deterministic Malaria transmission model by considering the recovered population with and without immunity. A transmission model is found to be useful in providing a better understanding on the disease and the impact towards the human population. In this research, two possibilities were taken into account where one possibility is that infectious humans do not gain immunity while another possibility is that infectious humans will gain temporary immunity. The mathematical model is developed based on the SEIR model which has susceptible SH, exposed EH, infectious IH and recovered RH classes. The system of equations which were obtained were solved numerically and results were simulated and analyzed. The analysis includes the impact of the different values of the average duration to build effective immunity on the infectious humans. We observed that when the value of q, per capita rate of building effective immunity is increased, the maximum number of infected humans decreased. Hence, if an effective immunity can be build in a short period of time for those who recover from the disease, the number of cases could be reduced.